Korelasi Pemahaman Materi Riya dengan Menjauhi Perilaku Humblebrag Era Milenial pada Peserta Didik (Bedelau: Journal of Education and Learning, 2021)
This study aims to determine the correlation between understanding of riya material by staying away from behavior humblebrag among millennial erastudents of 03 Tapung Public Senior High School, Pekanbaru Regency. The population in this study were all students of class XI totaling 146 students. The research sample was 25% or 36 students. Sampling using proportional sampling technique. The data collection techniques used were tests, questionnaires, and documentation. The data analysis technique used to test the hypothesis in this study is thecorrelation product moment. Based on the results of thecorrelation test, product moment it can be concluded that the correlation of understanding of real material by staying away from behavior humblebrag millennial erain high school students 03 Tapung, Kampar district is 0.852. It can be interpreted the coefficient value using the interpretation table of the correlation coefficient and the"r" value Product Moment. With df = 36-2 = 34, it can be seen that rtable at a significant level of 5% = 0.329. So this shows that rxy = 0.852> rtable > 0.329 at a significant level of 5%, which means that the null hypothesis is rejected and the alternative hypothesis is accepted, which means that there is a significant correlation between understanding the real material and staying away frombehavior humblebrag millennial erain class XI students. at 03 Tapung Public Senior High School.